Identifying patients at risk of inpatient aggression at the time of admission to acute mental health care. What factors should clinicians consider?. (3rd July 2017) - Meehan, Tom; de Alwis, Angelo; Stedman, Terry
ABSTRACT: Objective: The aim of this study was to identify, at the time of admission, predictors of aggression in adults admitted to acute mental health care. Method: Adult patients ( n = 350) consecutively admitted to the National Institute of Mental Health (NIMH) in Sri Lanka were assessed for a wide range of dispositional, historical, contextual and clinical factors associated with inpatient violence. Clinical factors were assessed using the Brief Psychiatric Rating Scale (BPRS), and risk of aggression using the Brøset Violence Checklist (BVC). All 350 patients were followed for 72 hours post-admission and observed for aggression using the Overt Aggression Scale. Results: Fifty-nine patients (16.8%) met criteria for aggression. Those in the aggressive group were younger, single and had caused harm to others or damaged property in the two weeks prior to admission. Aggressive patients were also more likely to exhibit symptoms of psychopathology (higher scores on the hostility-suspiciousness subscale of BPRS) and to have a higher total score on the BVC at the time of admission, than other patients. Conclusions: Of all of the risk factors considered at the time of admission, the BVC total score was the strongest predictor of aggression following admission. Indeed, the BVC was a more robust predictor of aggression in the post-admission period than a history of aggression preceding admission and psychopathology as measured by the BPRS. The finding supports the use of structured risk assessments for monitoring the risk of aggression in patients during the initial 72 hours post-admission.